Analysis of the Implementation of Bioaugmentation in the Remediation of Petroleum-Contaminated Soils in Oil and Gas Exploration Areas - Tengku Fachrur Reza; Budijono Budijono; Suwondo Suwondo (Green Publisher Indonesia, 2026)
This study analyzes the impact of ecological remediation through bioaugmentation techniques to remediate crude oil-contaminated soil and its social and economic implications in Siak Regency, Riau Province. Oil contamination caused by leakage due to illegal tapping of oil pipelines has become a serious environmental issue requiring effective and sustainable remediation methods. This study aims to evaluate the effectiveness of bioaugmentation in reducing long-chain petroleum hydrocarbons (C10–C36) to meet environmental quality standards while also assessing the social and economic impacts of its implementation. A mixed-methods approach was applied, combining quantitative analysis of laboratory test results and environmental monitoring with qualitative surveys and interviews involving communities, government agencies, and companies. The results show that bioaugmentation using indigenous bacteria significantly reduced petroleum hydrocarbon concentrations from 8.4%–9.4% to below the environmental quality standard (≤0.1%) within 5–6 weeks. The most efficient dosage was found to be 1 liter/m³ of contaminated soil, as it achieved degradation rates comparable to those of 2 liters/m³ but with lower operational costs. Environmental conditions during remediation remained optimal for microbial activity, with a pH of 6.0–6.9, a temperature of 26–36 °C, and humidity of around 70%. Socially and economically, the implementation received positive responses, although community satisfaction was slightly lower than that of government agencies and companies. Overall, bioaugmentation was proven to be an effective, economical, and environmentally friendly remediation technology for the sustainable recovery of crude oil-contaminated soil.